NATURAL BIODEGRADATION OF COPROSTANOL IN AN EXPERIMENTAL SYSTEM OF THREE ENVIRONMENTAL CONDITIONS OF JAKARTA WATERS, INDONESIA - Tonny Bachtiar; Agus Sabdono (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Constraint of using bio-indicator (coliform bacteria) as an indicator of domestic (sewage) pollution in the environment with high environmental stress encourages the discovering of other alternate indicators. Coprostanol has been proposed as a chemical indicator of domestic waste pollution, but most research on were conducted in the temperate (high latitude) region. The persistence of coprostanol in tropical region, especially in Indonesia, is still very poor. It is very important to understand the persistence of coprostanol in the nature, as one of the requirements to propose coprostanol as an alternate indicator of domestic waste pollution. In order to better understand the natural biodegradation of coprostanol, experimental system on three environmental conditions (river, river mouth, and coastal waters) was conducted. In April 2004, samples of water and surface bottom sediments were collected from each environmental condition in duplicate. Before the samples were put into aerated and non-aerated aquaria, about 35-40 g of surface bottom sediments were taken to analyze the initial concentration (C0) of coprostanol. The sediments were subsequently sampled from each aquarium within a certain interval day to analyze the concentration of coprostanol (C10, C20, and C40). The results showed that aeration plays not an important role in natural biodegradation of coprostanol. In average, the highest rate of coprostanol biodegradation is 0.438 μg/g day-1 in non aerated coastal water environment, where as the lowest was found in the non aerated river mouth environment (0.021 μg/g day-1). Since coprostanol was degraded very slowly, and could be detected in the sediments of three environmental conditions, coprostanol has an excellent potency to be used as an alternate indicator of domestic wastes.